Pseudomonas strains from the Livingston Island, Antarctica: a source of cold-active hydrolytic enzymes (2022)
Pseudomonas spp. is considered one of the most successful bacterial genera due to its plasticity and metabolic versatility, which has allowed it to colonize different ecosystems, including Antarctica. The ability of Pseudomonas to adapt an d survive in the hostile conditions of the Antarctic makes them a reservoir of enzymes that can be used in different biotechnological applications; however, research on this genus in Antarctica is still in its infancy. Therefore, the aim of this study was to isolate and characterise cold-adapted Pseudomonas from Livingston Island, Antarctica, and expl ore th eir abi l ity to produce cold-active hydrolytic enzymes. In the present study, we isolated seven cold-adapted bacteria related to the genus Pseudomonas. The isolated strains have the ability to produce hydrolytic enzymes. These results demonstrate that cold-adapted Pseudomonas from Antarctica are a promising source of cold-active enzymes with biotechnological potential.